A Three‐Membered Diazo‐Aluminum Heterocycle to Access an Al=C π Bonding Species. (19th September 2022) - Yan, Chenting; Kinjo, Rei
Abstract: [1+2] cycloaddition between a cyclic (alkyl)(amino)aluminyl anion (3 ) and diaryldiazomethane affords an AlN2 three‐membered ring species (4 ). Compound (4 ) is thermally unstable and spontaneously releases N2 gas under the mild reaction condition to generate an ion‐separated species 5 . An X‐ray study shows that the anionic part of 5 bears a considerable short exocyclic Al−C bond, and computational studies involving molecular orbital and natural bond orbital analysis indicate the Al=C π bonding character. The Al=C moiety of 5 undergoes intramolecular C−H activation. Moreover, reaction of 5 with a diazo compound leads to the reduction and complete cleavage of the N=N double bond. Abstract : [1+2] cycloaddition between a cyclic (alkyl)(amino)aluminyl anion and diaryldiazomethane affords an AlN2 three‐membered ring species. This compound is thermally unstable and spontaneously releases N2 to generate an ion‐separated species featuring a significantly short Al−C bond with Al=C π bonding character. The Al=C moiety does not only undergo intramolecular C−H activation, but intermolecularly cleaves the N=N double bond of a diazo compound.